Soluble fibrinogen‐like protein 2 ameliorates acute rejection of liver transplantation in rat via inducing Kupffer cells M2 polarization. (10th May 2018) - Pan, Guangrui; Zhao, Zhengfei; Tang, Chengyong; Ding, Liuyue; Li, Zhongtang; Zheng, Daofeng; Zong, Liang; Wu, Zhongjun
Abstract: Soluble fibrinogen‐like protein 2 (sFGL2) could ameliorate acute rejection (AR) in rat cardiac transplantation. However, the role of sFGL2 in AR of liver transplantation has not been addressed. In this study, we found that FGL2 was upregulated in rat orthotropic liver transplantation (OLT) models of tolerance and positive correlation with the frequency of M2 Kupffer cells (KCs). Gain‐of‐function experiments in vitro showed that sFGL2 promoted the secretion of anti‐inflammatory cytokines (IL‐10, TGF‐β) and the expression of CD206, and inhibited the activities of STAT1 and NF‐κB signaling pathway. Consistently, in vivo assays showed that adeno‐associated virus‐mediated FGL2 (AAV‐FGL2) transfer to recipients could ameliorate AR of rat OLT and induce KCs M2 polarization in allografts. Notably, we found that the recipients receiving transferred KCs from AAV‐FGL2‐treated allograft showed alleviated AR. Taken together, we revealed that sFGL2 ameliorated AR by inducing KCs M2 polarization. Abstract : In vivo assays showed that adeno‐associated virus‐mediated FGL2 (AAV‐FGL2) transfer to recipients could ameliorate AR of rat OLT and induce KCs M2 polarization in allografts. Notably, we found that the recipients receiving transferred KCs from AAV‐FGL2‐treated allograft showed alleviated AR. Taken together, we revealed that sFGL2 ameliorated AR by inducing KCs M2 polarization.